Attitudes to integrated reporting in small-to medium-sized companies - Du Bourg, Caroline (My University, 2018)
The purpose of this research is to explore the attitudes of small- to medium-sized entities (SMEs) towards integrated reporting. This report analyses the motivations to produce an integrated report, the reasons for not preparing one, the isomorphic processes present in the field, and the logics of resistance evident. The thesis employs an interpretive methodology. Interviews were held with a sample of professionals involved with corporate reporting for SMEs’ to establish their attitudes towards preparing integrated reports. These attitudes were then analysed to identify the key themes. The research finds that the respondents perceive the primary benefits of preparing an integrated report to be improved relationships with stakeholders and an enhanced strategy and business model. Cost, lack of resources and no buy-in to the concept are the reasons that were identified for not SMEs to not adopt integrated reporting. The benefits are currently overshadowed by the perceived challenges which results in limited isomorphic pressures present in the field to engender the change. SMEs preparing integrated reports understand them to be best-practice. In contrast, those that do not prepare integrated reports disagree with this claim, as they are unaware of the topic or do not believe it to be applicable in the smaller environment. These attitudes have resulted in logics of resistance. The resistance has taken the form of either not preparing reports or not adhering to the essence of the concept. However, there is also evidence that some SMEs have complied with the requirements of integrated reporting. The research further revealed that the interaction between the isomorphic processes and logics of resistance determines the extent to which an SME prepares an integrated report. The results of this thesis indicate that the isomorphic pressures within the field need to grow to stimulate further preparation of reports. To achieve this, there needs to be widespread instruction on the topic, as well as an adaptation of the framework to be more relevant for smaller entities. This research shows how a social context impacts isomorphic processes and how the relatively new concept of integrated reporting is applied in an SME environment. The interpretive-style financial reporting research that has been employed addresses a void in the existing literature.
A research report submitted by Caroline Du Bourg In partial fulfilment of the degree of Masters of Commerce in the field of Accounting, University of the Witwatersrand, Johannesburg, 2018
Keywords: Small- to medium-sized entities (SMEs); Isomorphic processes; Concept of integrated reporting; UCTD; Small business; Entrepreneurship; Small business--South Africa; SDG-8: Decent work and economic growth